Comprehensive assessment of knee joint synovitis at 7 T MRI using contrast-enhanced and non-enhanced sequences - Christoph Treutlein; Tobias Bäuerle; Armin M. Nagel; Ali Guermazi; Arnd Kleyer; David Simon; Georg Schett; Tobias Hepp; Michael Uder; Frank W. Roemer (BMC Musculoskeletal Disorders, 2020)
Abstract Background Seven T ultra-high field MRI systems have recently been approved for clinical use by the U.S. and European regulatory agencies. These systems are now being used clinically and will likely be more widely available in the near future. One of the applications of 7 T systems is musculoskeletal disease and particularly peripheral arthritis imaging. Since the introduction of potent anti-rheumatic therapies over the last two decades MRI has gained increasing importance particularly for assessment of disease activity in early stages of several rheumatic disorders. Commonly gadolinium-based contrast agents are used for assessment of synovitis. Due to potential side-effects of gadolinium non-enhanced techniques are desirable that enable visualization of inflammatory disease manifestations. The feasibility of 7 T MRI for evaluation of peripheral arthritis has not been shown up to now. Aim of our study was to evaluate the feasibility of contrast-enhanced (CE) and non-enhanced MRI at 7 T for the assessment of knee joint synovitis. Method Seven T MRI was acquired for 10 patients with an established diagnosis of psoriatic or rheumatoid arthritis. The study pulse sequence protocol was comprised of a sagittal intermediate-weighted fat-suppressed (FS), axial fluid-attenuated inversion recovery (FLAIR) FS, sagittal 3D T1-weighted dynamic contrast enhanced (DCE) and an axial static 2D T1-weighted FS contrast-enhanced sequence (T1-FS CE). Ordinal scoring on non-enhanced (Hoffa- and effusion-synovitis) and enhanced MRI (11-point synovitis score), and comparison of FLAIR-FS with static T1-FS CE MRI using semiquantitative (SQ) grading and volume assessment was performed. For inter- and intra-reader reliability assessment weighted kappa statistics for ordinal scores and intraclass correlation coefficients (ICC) for continuous variables were used. Results The total length of study protocol was 15 min 38 s. Different amounts of synovitis were observed in all patients (mild: n = 3; moderate: n = 5; severe: n = 2). Consistently, SQ assessment yielded significantly lower peripatellar summed synovitis scores for the FLAIR-FS sequence compared to the CE T1-FS sequence (p < 0.01). FLAIR-FS showed significantly lower peripatellar synovial volumes (p < 0.01) compared to CE T1-FS imaging with an average percentage difference of 18.6 ± 9.5%. Inter- and intra-reader reliability for ordinal SQ scoring ranged from 0.21 (inter-reader Hoffa-synovitis) to 1.00 (inter-reader effusion-synovitis). Inter- and intra-observer reliability of SQ 3D-DCE parameters ranged from 0.86 to 0.99. Conclusions Seven T FLAIR-FS ultra-high field MRI is a potential non-enhanced imaging method able to visualize synovial inflammation with high conspicuity and holds promise for further application in research endeavors and clinical routine by trained readers.